A laboratory Study on the Effect of Perforated Sills in Stilling Basin on the Secondary Depth and Length of the Roller of the Hydraulic Jump - R. Khankhani Zorab; S. M. Kashefipour (علوم آب و خاک, 2018)
The purpose of this study was to evaluate two perforated sills in the stilling basin and their impact on characteristics of the hydraulic jump, such as the length of the roller of hydraulic jump, decrease in the secondary depth of the hydraulic jump, and the required tailwater depth. Also, the optimal distance of two perforated sills from the beginning of the stilling basin with a fixed height for the perforated sill and ratios of the opening of holes equal to 50% were determined. The experiments were carried out in the form of 48 tests for different discharges in the range of 47 to 145 lit/s and for Froude numbers in range of 3.6 to 11.2. The results of the experiments on two perforated sills showed that they could only reduce the length of the roller of the hydraulic jump to an acceptable level, with the distance between them providing the conditions to create a stable jump; also, the length of roller of jump was not decreased by reducing the distance between the sills. Also, they decreased the secondary depth of the forced hydraulic jump up to 27.8%, which was less than the secondary depth of the free hydraulic jump; the length of roller was up to 76.9 % less than the length of the roller of the free hydraulic jump for the Froude number of 11.2.